Pattern of Chest X-rays findings and clinical correlation with the severity in COVID-19 (RT-PCR positive) infected patients admitted in a COVID-19 dedicated hospital in Bangladesh (Bangladesh Journal of Medicine, 2022)
Objective: This study aims to analyze Chest X-ray findings in COVID 19(RT-PCR positive) patients, correlate between clinical and radiological findings and short-term outcomes of the patients with the view to enhance clinicians’ understanding of CXR findings in COVID 19 patients.Methods: This descriptive type of observational study included 277 reverse transcriptase-polymerase chain reaction (RT-PCR) confirmed COVID-19 patients who were undergone CXRs, based on the clinician’s decision. Data were collected from May to September 2020 of Maternal and Child Health Training Institute (MCHTI)- a COVID-19 dedicated hospital, Lalkuthi, Mirpur-1, Dhaka and analyzed statistically through SPSS,Version 25. Each chest X-Ray is then scored using the Brixia score, a semi-quantitative scoring system rating lung involvement from 0 to 18 by a radiologist. The scores are then analyzed and compared with the characteristics of the patients, clinical presentation, and short-term outcome (in-hospital & after discharge) to correlate the severity and post covid-19 complications of COVID-19 infected patients.Results: A total of 277 RT-PCR-positive patients were performed chest x-ray P/A view, among them 58.12%(161) were male and 41.88%(116) were female. Age variation was from 6 to 95 years and the mean age was 42.48±15.53(S.D).Most of the patients(94.94%)were symptomatic and the majority(97.9%) of symptomatic patients had comorbidities(p-value 0.02).Among the x-ray performed patients(n=277), 39.35% (109) patients had positive findings suggestive of covid-19 infection. Comorbidities and sex had significant relation on positive x-ray findings(p-value 0.0001 and 0.001);males (70.6%) had more positive findings than females(29.4%).Positive x-ray findings were more common among the age group 41 to 60 years (p-value 0.0001 and Cramer’s V 0.59).Most of the patients (94.49%) had bilateral lungs involvement and consolidations were the commonest x-ray findings (43.1%).Clinical severity was assessed by symptoms and Spo2 level (8) had a significant relation to clinical severity (p-value 0.0001,0.0001&0.0001) and sex also influences clinical severity though statistically not significant (p-value 0.2).There was a significant relationship between positive X-Ray findings and decreased Spo2 level (p-value 0.0001, Cramer’s V 0.47).Regarding in-hospital outcome; 94.9% were recovered and 2.75%were death (only male)and following discharge; 42.60% (119) had post covid-19 complications and 0.72% (02) were dead. Comorbidities and age had an effect on short-term outcomes after hospital discharge though not statistically significant (p-value 0.16 and 0.16). The most common respiratory complications were SOB on exertion (23) and the most common non-respiratory complication was post covid fatigue syndrome (42). Comparison between Brixia score and post covid complications; more the Brixia score, the more the chance of post covid complications though statistically not significant (p-value 0.44).Conclusion: This study reveals bilateral lungs involvement and multifocal consolidations are the most common patterns of X-ray findings and clinical severity is associated with a higher Brixia score, male sex, increasing age, and presence of comorbidities.Bangladesh J Medicine 2022; 33: 280-292